The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1590/s1413-86702011000500011
|View full text |Cite
|
Sign up to set email alerts
|

Detection of SPM and IMP metallo-β-lactamases in clinical specimens of Pseudomonas aeruginosa from a Brazilian public tertiary hospital

Abstract: Phenotypic and genotypic SPM and IMP metallo-β-lactamases (MBL) detection and also the determination of minimal inhibitory concentrations (MIC) to imipenem, meropenem and ceftazidime were evaluated in 47 multidrug-resistant Pseudomonas aeruginosa isolates from clinical specimens. Polymerase chain reaction detected 14 positive samples to either bla SPM or bla IMP genes, while the best phenotypic assay (ceftazidime substrate and mercaptopropionic acid inhibitor) detected 13 of these samples. Imipenem, meropenem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…IMP is also considered one of the most important types of MBLs. Camagaro et al, (2011) reported that after being restricted for more than ten years to Brazilian hospitals; SPM seems to become a global challenge, warning for the role of human traffic in spreading MBL genes (Salabi et al, 2010).…”
mentioning
confidence: 99%
“…IMP is also considered one of the most important types of MBLs. Camagaro et al, (2011) reported that after being restricted for more than ten years to Brazilian hospitals; SPM seems to become a global challenge, warning for the role of human traffic in spreading MBL genes (Salabi et al, 2010).…”
mentioning
confidence: 99%
“…The limitations of this present systematic review and meta-analysis conducted in Brazil lie in terms of the search methodology applied (due to the use of specific keywords for the topic) and the inclusion of studies focusing on evaluating MβL detection by molecular methods, even though some include data on phenotypical detection. Also, in this meta-analysis, only original articles were included; however, it was observed that there are articles, mainly in a short communication format, which were excluded, which reported a high frequency of MβL and SPM-1 gene-producing strains in the Brazilian regions, which demonstrates that the estimated prevalence of MβL and SPM-1 may still be underestimated in their epidemiological natures [ 44 , 93 , 94 , 95 ]. Even though other sources may have been excluded from this review due to their in-depth profile or lack of high-quality evidence, this article denotes a good standard of methodological and scientific evidence and provides a basis for one-health strategies and new studies on this topic.…”
Section: Discussionmentioning
confidence: 99%